1985
DOI: 10.1017/s0022172400062665
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and significance of salmonella carriage by gulls (Larus spp.) in Scotland

Abstract: SUMMARYSalmonella carriage in 5888 gulls sampled by cloacal lavage was found to be 7-8 %. Marked geographical and seasonal differences in carriage rates were found.These differences appeared to be associated with human population density and seasonal differences in the reported incidence of human salmonellosis. The maximum duration of salmonella excretion in 17 laboratory-maintained gulls was 4 days and the number of salmonellae excreted was never more than 170 per gram of faeces. On the basis of this study it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 32 publications
4
45
0
1
Order By: Relevance
“…We suggest that the objects detected are oocysts of the genus Cryptosporidium because they conform to the following criteria: (a) smooth, thick-walled spherical or slightly ovoid bodies measuring [4][5][6] ,um, containing four banana-shaped inclusions, without sporocysts, when viewed in suspension under Nomarski optics, (b) the DNA selective fluorogenic dye, DAPI. highlighted four nuclei which 140 appeared to be within these banana-shaped inclusions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We suggest that the objects detected are oocysts of the genus Cryptosporidium because they conform to the following criteria: (a) smooth, thick-walled spherical or slightly ovoid bodies measuring [4][5][6] ,um, containing four banana-shaped inclusions, without sporocysts, when viewed in suspension under Nomarski optics, (b) the DNA selective fluorogenic dye, DAPI. highlighted four nuclei which 140 appeared to be within these banana-shaped inclusions.…”
Section: Discussionmentioning
confidence: 98%
“…oocyst environmental contamination for reasons similar to those suggested by Girdwood and colleagues for Salmonella spp. [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation of high numbers of microbes to organic matter can be anticipated as input of organic matter from plant production supports growth of microbial heterotrophic soil microbial communities (Fenchel et al, 2012;Roesch et al, 2007;Schlesinger, 1997;Whitman et al, 1998). It has also been demonstrated that a high number of viable counts of environmental bacteria and high organic matter could signify a more diverse groups of bacteria such as coliforms, faecal coliforms, Escherichia coli, and aerobic and anaerobic bacteria growing at 30 • C, and even pathogenic bacteria (Girdwood et al, 1985;Pommepuy et al, 1992). Consequently, samples in this study that showed significantly high number of environmental bacteria and few other samples with low bacterial counts were selected for further investigation to measure coliforms and the presence of pathogenic microbes such as Listeria, Campylobacter and Salmonella.…”
Section: Surface Soil Samplesmentioning
confidence: 99%
“…Kloakal svaplı TPS'ler 37°C'de 24 saat inkubasyona bırakılarak ön zenginleştirme işlemi yapıldı (14,11).Yumurtaların 10 adeti steril şartlarda kırılarak içerikleri steril seramik kaba aktarıldı. Yumurta içeriği steril şartlarda homojenize edildikten sonra 25 gr alınıp 225 ml TPS bulunan erlenmayerlere aktarıldı.…”
Section: Kloakal Svap Ve Yumurta Içeriğinden Salmonella Izolasyon çAlunclassified